Живая идея – основа продуктивной работы профессионально-сетевого сообщества в школе - Горжуй, Л.Н. (My University, 2016)
The article deals with the definite experience, the real practice of the networks “Scaffolders” of secondary school #1 named after G. Dimitrov. The article gives the reader some data on efforts to provide interactive support of the colleagues with the purpose of conversion teaching practice and creating collaborative school environment. The targeted focus of the article is for the certified teachers of secondary schools.
Keywords: project; problem; certified; coaching; teacher